Nonlinear, Tunable and Active Metamaterials - Shadrivov, Ilya V (Springer, 2016)
Metamaterials, artificial electromagnetic media achieved by structuring on the subwave-length-scale were initially suggested for the negative index and superlensing. They became a paradigm for engineering electromagnetic space and controlling propagation of waves. The research agenda is now shifting on achieving tuneable, switchable, nonlinear and sensing functionalities. The time has come to talk about the emerging research field of metadevices employing active and tunable metamaterials with unique functionalities achieved by structuring of functional matter on the subwave-length scale. This book presents the first systematic and comprehensive summary of the reviews written by the pioneers and top-class experts in the field of metamaterials. It addresses many grand challenges of the cutting edge research for creating smaller and more efficient photonic structures and devices